IDENTIFICATION DES CAUSES DE L’INSECURITE DANS LE PARC NATIONAL DES VIRUNGA EN TERRITOIRE DE NYIRAGONGO - Master ENOCK AMANI ALYCIEN (IJRDO - Journal of Social Science and Humanities Research, 2024)
Insecurity being the lack of peace of mind, but also the absence of a situation where one find oneself in the state of seeing that no danger is to be feared, this phenomenon in the world continues to manifest itself in protected areas as in national parks and this affects the local populations who encounter several difficulties of all kinds. Insecurity everywhere as in national parks does not come from chance but is due to several factors, this study is part of the identification of the causes of insecurity in the Virunga National Park in Nyiragongo territory found in the province of North Kivu in the Democratic Republic of Congo. It notes the fact that natural resources are victims of external events that damage their development. The observation is that the Virunga National Park is a victim of insecurity manifesting itself on a large scale and has repercussions on the populations living in the Nyiragongo territory, particularly those of the Kibumba group, our target for the surveys. The focus group discussion, descriptive methods, face-to-face interview methods are methods that have been used to arrive at the point of finding the results in the data collection according to the assessments of the respondents. After the data collection work, it was noticed that conflicts between farmers and unemployment are major factors that cause large-scale insecurity in this park according the populations surveyed while signifying that the causes are numerous Beyong these two major causes, poverty, poor governance, conflicts over arable land, the nonintegration of local populations into the hierarchical staff of park management, and the ignorance of the population are other factors that are the source of insecurity in the Virunga National Park.